Satellite Massive Array With Reconfigurable Antenna Units for Long-Life and Energy Saving Satellites - Francesco Alessio Dicandia; Simone Genovesi (IEEE Access)
A synergic cooperation between terrestrial and non-terrestrial networks is a pivotal feature for achieving global wireless coverage. In this framework, the satellite swarm-based massive array represents one of the most promising key enabling technologies in coping with the ever-increasing system requirements for beyond 5G (B5G) and 6G systems. In this paper, a novel strategy for the synthesis of satellite massive arrays with reconfigurable antenna units (SMART-U) is presented. The radiative performance of the proposed configuration are analysed for low-earth and geostationary orbiting satellites and assess a remarkable robustness and flexibility of the new synthesis architecture. A remarkable scanning range improvement and peak side lobe level (PSLL) lowering of the addressed concentric ring array (CRA) is achieved by exploiting a multiobjective optimization based on the Pareto front. The proposed SMART-U phased array can efficiently cope with adverse satellite attitudes by tailoring the circularly polarized (CP) field radiated by each unit offering a clear advantage with respect to conventional swarm-based arrays with a static antenna element factor.